QURAMALÍ KÓRSETKISHLI- DÁREJELI TEŃLEMELERDI SHESHIW USÍLLARÍ - Djumabaev, N. (SCIENCE and SOCIETY, 2024)
The article contains examples and problems that will further increase students’ interest in mathematics. These examples and tasks are of great importance in the formation of their knowledge and skills. It is very important to increase the interest of students interested in mathematics and teach them to solve logical problems.